Regulatory function of CD4+CD25++ T cells in patients with myasthenia gravis is associated with phenotypic changes and STAT5 signaling: 1,25-Dihydroxyvitamin D3 modulates the suppressor activity - Alahgholi-Hajibehzad, Mahdi; Marx, Alexander (Journal of neuroimmunology, 2015)
Regulatory T cells were investigated in early-onset (EO) and late-onset (LO) myasthenia gravis patients with anti-acetylcholine receptor antibody (AChR-MG). Alterations in PD-1 and PD-L1 on CD4+CD25++ (Treg) and responder T cells (Tresp, CD4+CD25−) were observed in LOMG patients. GITR was decreased on CD4+CD25++ of all patients. Decrease of FOXP3 was associated with lower phosphorylation of STAT5.1,25-dihydroxyvitamin D3 (VitD3) increased suppression in co-culture with a stronger effect in patients by acting possibly both on cell groups. Changes in surface molecules and intracellular pathways contribute to the defects of Treg in non-thymomatous AChR-MG and VitD3 can have modulatory effects.